Pemberdayaan Ekonomi dan Kewirausahaan: Mengatasi Monotoni Sumber Mata Pencaharian Turun Temurun di Desa Telaga Jernih - Julia Rafika; Uswah Hasanah (Lembaga Pengembangan Kinerja Dosen, 2024)
Real Work Lecture (KKN) is a community service program by students that aims to empower the community with a cross-disciplinary and sectoral approach. The KKN program in Telaga Jernih Village, Secanggang District, Langkat Regency, aims to overcome the problem of monotonous hereditary livelihoods and open up new business opportunities through economic empowerment and entrepreneurship. Before the program was implemented, most villagers relied on the agricultural sector, especially oil palm and rice, which made the village economy vulnerable to price fluctuations and environmental conditions. This program focused on socialization about livelihood diversification, entrepreneurial skills training, and reducing plastic waste by converting it into products with economic value. Through this training, the community was invited to see local potential that could be developed into new business opportunities. The results of the implementation of this KKN showed an increase in community understanding of the importance of business diversification and the application of skills acquired in starting small businesses in the fields of agricultural processing and plastic waste recycling. Several residents have started new businesses supported by the skills taught during the training. However, several challenges such as low digital literacy and limited access to capital are still obstacles to business development. Therefore, a follow-up program is needed that focuses on developing digital skills and access to capital to support the sustainability of the business that has been pioneered. Overall, this KKN program has succeeded in providing a positive impact on the Telaga Jernih Village community and can be a model for local potential-based economic empowerment in other villages.